Zadania proboszcza w zakresie poradnictwa rodzinnego - Adamczyk, Jerzy (Ius Matrimoniale, 2017)
The author of the following article focused on an important canonic-pastoral problem, which is the issue of the preacher’s tasks in the family counselling field. The aim of this article was to depict the duties of the peacher in the area of preparations for the marriage, furthermore, to present the preacher’s responsibility to organise and run the catholic marriage and family clinic. The preacher should also take care of appropriate people to work at the clinic, as well as their training.